Analisis Efektivitas Build Up Timnas Indonesia di Asean Mitsubishi Electric Cup 2024 - Dwi P, Ajodyo Yogo; Apriliyanto, Rizki; Sulaiman, Ahmad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
The purpose of this study is to determine the effectiveness of the build up of the Indonesian national team in the Asean Mitsubishi Electic Cup 2024. Indonesian national team at the Asean Mitsubishi Electic Cup 2024 and as a recommendation for coaches and players to implement build-up strategies in the future. This research method is quantitative research, with a descriptive approach method. The population used is the entire Indonesian national team match, the research technique is watching live recordings or videos of matches. Based on the results of the study, it can be concluded that the build up from various areas is as follows: from the left side, there were 23 successful build up attempts with a percentage of 65.2% and those that failed were 34.8%. Meanwhile, from the center area, there were 18 successful build up attempts reaching 77.8% and 22.2% failed. On the right side, build ups were recorded as many as 14 attempts, with a success percentage of 42.9% and failure of 57.1%. The Indonesian national team was more effective in building up from the center, which managed to utilize the center of the field well to build up the attack. attack. Keywords: Build up, Failure, Effectiveness, Success